Evaluation of certain crop residues for carbohydrate and protein fractions by cornell net carbohydrate and protein system - Swarna, Venkateswarulu; Dhulipalla, Srinivas Kumar; Elineni, Raghava Rao; Dhulipalla, Narendra Nath (Journal of Advanced Veterinary and Animal Research, 2015)
Four locally available crop residues viz., jowar stover (JS), maize stover (MS), red gram straw (RGS) and black gram straw (BGS) were evaluated for carbohydrate and protein fractions using Cornell Net Carbohydrate and Protein (CNCP) system. Lignin (% NDF) was higher in legume straws as compared to cereal stovers while Non-structural carbohydrates (NSC) (% DM) followed the reverse trend. The carbohydrate fractions A and B1 were higher in BGS while B2 was higher in MS as compared to other crop residues. The unavailable cell wall fraction (C) was higher in legume straws when compared to cereal stovers. Among protein fractions, B1 was higher in legume straws when compared to cereal stovers while B2 was higher in cereal stovers as compared to legume straws. Fraction B3 largely, bypass protein was highest in MS as compared to other crop residues. Acid detergent insoluble crude protein (ADICP) (% CP) or unavailable protein fraction C was lowest in MS and highest in BGS. It is concluded that MS is superior in nutritional value for feeding ruminants as compared to other crop residues. http://dx.doi.org/10.5455/javar.2015.b74